Hygiene, Sanitation and Bacteriological Quality of Cow's Milk in Krajan Design, Gendro Village, Tutur Regency of Pasuruan District - Ririn Indah Permatasari (Jurnal Kesehatan Lingkungan, 2018)
Cattle waste contains high enough Escherichia coli microbes that can contaminate dairy products. Contamination can come from various sources of cow udder, cow body, dust in the air, dirty equipment and humans who do milking. Hygiene and sanitation efforts are one of the most important environmental health efforts to prevent dairy contamination. This study aims to analyzed the relationship of hygiene breeders, sanitation cage and bacteriological quality of cow milk (Escherichia coli) in Krajan Hamlet, Gendro Village, Tutur District, Pasuruan Regency. This research was conducted with cross sectional design. The sample size used was the total population of 26 farmers registered to be members of the group of Agung II breeders in Krajan Hamlet. Breeder hygiene and cage sanitation were analyzed descriptively quantitatively on bacteriological quality of cow's milk (Escherichia coli). Breeder hygiene includes 3 components: the use of PPE when working (boots, masks, gloves), hand-washing habits and work clothing conditions. Cage sanitation includes 5 components namely the technical requirements of the cage building, the location of the cage, the direction of the cage, the handling of livestock waste, the cleanliness of the cage. Bacteriological qualities of cow's milk (Escherichia coli) were examined in the laboratory using isolation and identification techniques. As many as 73% of respondents included in the category of poor farmer's hygiene and 65% of respondents included in the category of poor cage sanitation. While the examination of milk samples as much as 65% is known to be contaminat Escherichia coli. Increas use of PPE (Personal Protective Equipment) and cage sanitation management needs to be done by farmers to prevent contamination of Escherichia coli in dairy products.